Gluconeogenesis, an essential metabolic pathway for pathogenic Francisella. Issue 3 (10th September 2015) - Brissac, Terry; Ziveri, Jason; Ramond, Elodie; Tros, Fabiola; Kock, Stephanie; Dupuis, Marion; Brillet, Magali; Barel, Monique; Peyriga, Lindsay; Cahoreau, Edern; Charbit, Alain
Summary Intracellular multiplication and dissemination of the infectious bacterial pathogen Francisella tularensis implies the utilization of multiple host‐derived nutrients. Here, we demonstrate that gluconeogenesis constitutes an essential metabolic pathway in Francisella pathogenesis. Indeed, inactivation of gene glpX, encoding the unique fructose 1, 6‐bisphosphatase of Francisella, severely impaired bacterial intracellular multiplication when cells were supplemented by gluconeogenic substrates such as glycerol or pyruvate. The ΔglpX mutant also showed a severe virulence defect in the mouse model, confirming the importance of this pathway during the in vivo life cycle of the pathogen. Isotopic profiling revealed the major role of the Embden–Meyerhof (glycolysis) pathway in glucose catabolism in Francisella and confirmed the importance of glpX in gluconeogenesis. Altogether, the data presented suggest that gluconeogenesis allows Francisella to cope with the limiting glucose availability it encounters during its infectious cycle by relying on host amino acids. Hence, targeting the gluconeogenic pathway might constitute an interesting therapeutic approach against this pathogen.